Ekyeyo Mobile Application - Nkuba, Blair; Kansiime, Daniel (Kabale University, 2025)
The Ekyeyo mobile application addressed critical inefficiencies in Uganda's job market by leveraging technology to enhance the job-seeking and hiring processes. With a national unemployment rate of approximately 9.2%, traditional job search methods like newspapers and physical job boards fail to effectively connect job seekers with employers, leaving only 20% of vacancies filled through formal channels. This study explored the development of Ekyeyo, a user-friendly Android-based job portal that bridges this gap. The app incorporates advanced search algorithms, tailored job recommendations, and streamlined candidate screening to improve job-matching accuracy. By implementing the Iterative Model for development, the researchers designed and tested a platform that empowers job seekers to access opportunities and simplifies the hiring process for employers. Field studies revealed significant user satisfaction due to the app's efficiency and usability, with features such as real-time notifications and intuitive interfaces highlighted as key strengths. This innovation promised to reduce unemployment, foster economic growth, and establish a transparent recruitment ecosystem in Uganda. Future enhancements, including AI integration and broader industry applications, aim to scale the app's impact further.